Dogs and Opossums Positive for Vaccinia Virus during Outbreak Affecting Cattle and Humans, São Paulo State, Brazil - Peres, Marina G. (Emerg Infect Dis, 2016)
During a vaccinia virus (VACV) outbreak in São Paulo State, Brazil, blood samples were collected from cows, humans, other domestic animals, and wild mammals. Samples from 3 dogs and 3 opossums were positive for VACV by PCR. Results of gene sequencing yielded major questions regarding other mammalian species acting as reservoirs of VACV.